2012
DOI: 10.2136/sh12-03-0011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Compaction on Soil Properties Along the Mormon Trail, South-Central Iowa, USA

Abstract: The literature contains many studies addressing various aspects of soil compaction, but few of those studies address long‐term (>30 yr), natural recovery of the soil from compaction. Here, natural soil recovery over a 146‐yr period is investigated by comparing the properties of Sharpsburg soils in the Mormon Trail to those alongside the trail at a location in south‐central Iowa. Bulk density samples were collected using rings of known volume for the upper 20 cm of the soil in 5‐cm depth increments. Bulk soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…More vegetation means more organic matter and more organic matter results in a lower bulk density (Fig. 2c) (Brevik and Fenton, 2012;Srinivasarao et al, 2014;Parras-Alcántara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More vegetation means more organic matter and more organic matter results in a lower bulk density (Fig. 2c) (Brevik and Fenton, 2012;Srinivasarao et al, 2014;Parras-Alcántara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies carried out on archaeological structures have been useful in soil research. Parsons et al (1962) used soils formed in dated archaeological features to estimate rates of soil formation, while archaeological sites (Sandor and Eash, 1991) and features (Brevik and Fenton, 2012;Brevik, 2013b) (Fig. 4) have been used to investigate long-term effects of human activity on soil processes and properties.…”
Section: Soils and Social Sciencesmentioning
confidence: 99%
“…In turn, war has caused long-term and even irreversible changes to soils, leaving them polluted with oil, organic chemicals, and heavy metals (Helmke and Losco, 2013). Here the trail appears as a zone of reduced vegetative productivity in this August photograph (Brevik and Fenton, 2012). (Right) A 2300-year-old cart trail at Castellar de Meca in eastern Spain.…”
Section: Soils and Social Sciencesmentioning
confidence: 99%
“…In some cases closure of recreational sites and trails can be a solution for trail degradation. However, to improve soil properties, long periods of closure are necessary due to slow soil-forming processes (Özcan et al, 2013;Sharratt et al, 1998;Brevik and Fenton, 2012). Another option is the importance role of trampling tolerant vegetation communities which can be both resistant and resilient to increased use (Pickering and Growcock, 2009).…”
Section: Decision Treesmentioning
confidence: 99%
“…To date, large amounts of research are focused on the impact of visitors on soil and vegetation including monitoring and modeling (Dixon et al, 2004;Farell and Marion, 2001;Monti and MacKintosh, 1979;Godefroid and Koedam, 2004;Özcan et al, 2013). A variety of efficient methods for evaluating trails and their resource conditions, especially in sensitive and vulnerable areas (alpine environment), have been developed and described in the literature (Jewell and Hammitt, 2000;Hawes et al, 2006;Ólafsdótirr and Runnström, 2013;Tomczyk and Ewertowski, 2011;Brevik and Fenton, 2012). A review by Marion and Leung (2001) concluded that the point sampling method provides accurate and precise measures of trail characteristics that are continuous or frequent (e.g., tread width).…”
Section: Introduction and Problem Overviewmentioning
confidence: 99%